2018
DOI: 10.1021/acs.jafc.8b01002
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation of Cyanidin-3-O-glucoside Enhances Protection Against UVB-Induced Epidermal Damage through Regulation of p53-Mediated Apoptosis in Mice

Abstract: Excess ultraviolet (UV) radiation causes numerous forms of skin damage. The aim of the present study was to assess and compare the photoprotective effects of cyanidin-3- O-glucoside (C3G) alone and encapsulated in chitosan nanoparticles (Nano-C3G) in a UVB-induced acute photodamage mouse model. Nano-C3G was developed from chitosan and sodium tripolyphosphate (TPP) by ionic gelation. The particle size, zeta potential, entrapment efficiency, drug loading, and in vitro release in 6 days were determined. Kunming (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…However, the p53 expression was significantly reduced in UVB‐irradiated cells after HPE treatment ( p < 0.01). These findings suggest that HPE regulated the cell apoptosis by reducing the generation of ROS, DNA damage, and p53 activation, which is consistent with the findings of previous studies (Hu et al, ; Liu, Hu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the p53 expression was significantly reduced in UVB‐irradiated cells after HPE treatment ( p < 0.01). These findings suggest that HPE regulated the cell apoptosis by reducing the generation of ROS, DNA damage, and p53 activation, which is consistent with the findings of previous studies (Hu et al, ; Liu, Hu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we need to determine whether C3G can penetrate into the skin and provide the possibility for anthocyanins as a functional factor for chronic photodamage. Our previous studies and others have shown that the characteristic absorption wavelengths of C3G are 279.9 and 519.3 nm (Liu et al., 2018; Ma et al., 2015). In this study, C3G was detected in the skin samples from the vitro experiment (Figure 1), it indicated that C3G can penetrate the skin.…”
Section: Discussionmentioning
confidence: 80%
“…found that delphinidin can target P47 phox , thereby inhibiting UVB‐induced ROS production (Lim et al., 2013). And our previous studies have shown that C3G scavenge ROS by decreasing EGFR phosphorylation in HaCaT cells, and C3G can also inhibit UVB‐induced the product of ROS including lipid peroxide and malondialdehyde in mice (He et al., 2017; Liu et al., 2018). Besides, C3G can inhibit UVB‐induced GSH depletion, lipid peroxidation and oxidative DNA damage (Pratheeshkumar et al., 2014).…”
Section: Discussionmentioning
confidence: 98%
“…CG is a potent antioxidant and protects against oxidative damage 157 . CG was also reported to reduce UVB-induced damage in vitro [158][159][160] and in vivo 161,162 .…”
Section: Chrysantheminmentioning
confidence: 93%